login

Year-end appeal: Please make a donation to the OEIS Foundation to support ongoing development and maintenance of the OEIS. We are now in our 61st year, we have over 378,000 sequences, and we’ve reached 11,000 citations (which often say “discovered thanks to the OEIS”).

A326936
Consider an empty list L, and for k = 1, 2, ...: if L contains a pair of consecutive terms summing to k, then let (u, v) be the first such pair: replace the two terms u and v in L with a single term k and set a(u) = -k and a(v) = +k, otherwise append k to L.
6
-3, 3, -7, 7, -11, 11, -18, -17, 17, -22, 18, 22, -27, 27, -31, 31, 35, -35, -39, 39, -44, -49, 44, 68, -51, 51, 49, -57, 57, -62, -70, 62, -67, 67, -84, -73, 73, -78, 70, 78, -83, 83, -88, -68, 88, -93, 93, -98, 84, 98, -108, -105, 105, -109, 109, -114, 108
OFFSET
1,1
COMMENTS
The sequence is well defined: sketch of proof, by contradiction:
- if the sequence were not well defined, then we would have some m > 0 such that L(1) = m for any k >= m,
- to prevent L(1) from being merged to L(2) forever, L(2) must always be merged to L(3) for some L(3) < m
- this can happen only finitely many times as the number of terms < m in L strictly decreases at each such merge,
- so at some time, L(1) < L(3) and L(1) merges with L(2) at k = L(1) + L(2), and then L(1) > m, a contradiction, QED.
The given procedure leads to a kind of infinite binary tree T:
- each node has a positive integer value,
- the node with value n has as parent the node with value abs(a(n)) and as sibling the node with value abs(a(n)) - n (see A328654 for the sibling of a node),
- each node has finitely many descendant nodes,
- each node has infinitely many ancestor nodes, so the tree is not rooted (see A328653 for the ancestors of 1),
- two nodes have always a common ancestor,
- see illustration in Links section.
FORMULA
If a(m) + a(n) = 0, then abs(a(m)) = abs(a(n)) = m + n.
EXAMPLE
For k = 1:
- we set L = (1).
For k = 2:
- we set L = (1, 2).
For k = 3:
- the first two terms, (1, 2), sum to 3,
- so a(1) = -3 and a(2) = +3,
- we set L = (3).
For k = 4:
- we set L = (3, 4).
For k = 5:
- we set L = (3, 4, 5).
For k = 6:
- we set L = (3, 4, 5, 6).
For k = 7:
- the first two terms, (3, 4), sum to 7,
- so a(3) = -1 and a(4) = +7,
- we set L = (7, 5, 6).
PROG
(C++) See Links section.
CROSSREFS
Sequence in context: A109579 A109580 A168269 * A336416 A128508 A083743
KEYWORD
sign
AUTHOR
Rémy Sigrist, Oct 22 2019
STATUS
approved